Answer:
Step-by-step explanation:
Whenever one of the equations gives an expression for one of the variables, it is useful to use that expression to substitute into the other equation.
Using the expression for y and substituting into the second equation, we have ...
3x -5(2 +1/4x) = -3
3x -10 -5/4x = -3 . . . . . . eliminate parentheses
7/4x = 7 . . . . . . . . . . . . . add 10, collect terms
x = 4 . . . . . . . . . . . . . . . . .multiply by 4/7
y = 2 + (1/4)(4) = 3
The solution is (x, y) = (4, 3).